Endocytosis of insulin at the blood-brain barrier - Pemberton, Sarah; Galindo, Demi C.; Schwartz, Michael W.; Banks, William A.; Rhea, Elizabeth M. (Frontiers in Drug Delivery, 2022)
For insulin to act within the brain, it is primarily transported from the blood across the blood-brain barrier (BBB). However, the endocytic machinery necessary for delivering insulin to the brain remains unknown. Additionally, there are processes within the brain endothelial cell that are designed to respond to insulin binding and elicit intracellular signaling. Using pharmacological inhibitors of different types of endocytosis (clathrin- vs caveolin-mediated), we investigated molecular mediators of both insulin BBB binding in isolated mouse brain microvessels and BBB insulin transport in mice studied by brain perfusion. We found clathrin-mediated mechanisms responsible for insulin surface binding in isolated brain microvessels while caveolin-mediated endocytosis may mediate BBB insulin transport specifically in the hypothalamus. These results further define the molecular machinery necessary for transporting insulin into the CNS and highlight the distinction between insulin internalization for transendothelial transport vs. intracellular signaling.